A Complementary Mechanism of Bacterial mRNA Translation Inhibition by Tetracyclines - Barrenechea, Victor; Vargas-Reyes, Maryhory; Quiliano, Miguel; Milón, Pohl (Frontiers in Microbiology, 2021)
Tetracycline has positively impacted human health as well as the farming and animal industries. Its extensive usage and versatility led to the spread of resistance mechanisms followed by the development of new variants of the antibiotic. Tetracyclines inhibit bacterial growth by impeding the binding of elongator tRNAs to the ribosome. However, a small number of reports indicated that Tetracyclines could also inhibit translation initiation, yet the molecular mechanism remained unknown. Here, we use biochemical and computational methods to study how Oxytetracycline (Otc), Demeclocycline (Dem), and Tigecycline (Tig) affect the translation initiation phase of protein synthesis. Our results show that all three Tetracyclines induce Initiation Factor IF3 to adopt a compact conformation on the 30S ribosomal subunit, similar to that induced by Initiation Factor IF1. This compaction was faster for Tig than Dem or Otc. Furthermore, all three tested tetracyclines affected IF1-bound 30S complexes. The dissociation rate constant of IF1 in early 30S complexes was 14-fold slower for Tig than Dem or Otc. Late 30S initiation complexes (30S pre-IC or IC) exhibited greater IF1 stabilization by Tig than for Dem and Otc. Tig and Otc delayed 50S joining to 30S ICs. Remarkably, the presence of Tig considerably slowed the progression to translation elongation and retained IF1 in the resulting 70S IC. Molecular modeling of Tetracyclines bound to the 30S pre-IC and 30S IC indicated that the antibiotics binding site topography fluctuates along the initiation pathway. Mainly, 30S complexes show potential contacts between Dem or Tig with IF1, providing a structural rationale for the enhanced affinity of the antibiotics in the presence of the factor. Altogether, our data indicate that Tetracyclines inhibit translation initiation by allosterically perturbing the IF3 layout on the 30S, retaining IF1 during 70S IC formation, and slowing the transition towards translation elongation. Thus, this study describes a new complementary mechanism by which Tetracyclines may inhibit bacterial protein synthesis.